2022
DOI: 10.1093/plphys/kiac016
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene response factor MdERF4 and histone deacetylase MdHDA19 suppress apple fruit ripening through histone deacetylation of ripening-related genes

Abstract: Histone deacetylase enzymes participate in the regulation of many aspects of plant development. However, the genome-level targets of histone deacetylation during apple (Malus domestica) fruit development have not been resolved in detail, and the mechanisms of regulation of such a process are unknown. We previously showed that the complex of ethylene response factor 4 (MdERF4) and the TOPLESS co-repressor (MdTPL4) (MdERF4-MdTPL4) is constitutively active during apple fruit development, but whether this transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…Combined with the result of Figure 5 A, we concluded that MdMADS6 targeted MdCCD1 and positively regulated the expression of MdCCD1 . To detect the regulating effect of MdHDA19 on MdCCD1 , we measured the MdCCD1 relative expression level in the ‘Orin’ apple calli overexpressed or silenced for MdHDA19 [ 19 ]. The results showed that the expression level of MdCCD1 decreased compared with the overexpressed pRI101 empty vector but increased significantly compared with overexpressed pRI101-RNAi empty vector, indicating that MdHDA19 negatively regulated the expression of MdCCD1 ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with the result of Figure 5 A, we concluded that MdMADS6 targeted MdCCD1 and positively regulated the expression of MdCCD1 . To detect the regulating effect of MdHDA19 on MdCCD1 , we measured the MdCCD1 relative expression level in the ‘Orin’ apple calli overexpressed or silenced for MdHDA19 [ 19 ]. The results showed that the expression level of MdCCD1 decreased compared with the overexpressed pRI101 empty vector but increased significantly compared with overexpressed pRI101-RNAi empty vector, indicating that MdHDA19 negatively regulated the expression of MdCCD1 ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…Malus domestica ‘Gala’ and MdHDA19 -transgenic ‘Orin’ apple calli were used in this study [ 19 ]. Fruits were harvested at 90–110 d after flower blossoming.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C/C and C/G alleles of MdERF4 at the EAR motif confer firm and soft texture respectively and other experiments indicate that MdERF4 affects firmness by reducing ethylene production by repressing MdERF3, a TF shown to be involved in the activation of ethylene biosynthesis by targeting MdACS1 (Hu et al, 2020). A recent study revealed a novel module, the MdERF4‐MdTPL‐MdHDA19 repressor complex that directly represses MdACS3a expression by decreasing the degree of histone acetylation, a critical epigenetic modification associated with transcriptional regulation (Hu et al, 2022). SlERF.F12, MaERF11, CpERF9 and MdERF4 have also been shown to recruit histone deacetylase and form a complex that targets CW genes, plus ethylene biosynthetic genes (Han et al, 2016; Fu et al, 2019; Deng et al, 2022; Hu et al, 2022) (Figure 4).…”
Section: Transcriptional Regulation Of Fleshy Fruit Softeningmentioning
confidence: 99%
“…A recent study revealed a novel module, the MdERF4‐MdTPL‐MdHDA19 repressor complex that directly represses MdACS3a expression by decreasing the degree of histone acetylation, a critical epigenetic modification associated with transcriptional regulation (Hu et al, 2022). SlERF.F12, MaERF11, CpERF9 and MdERF4 have also been shown to recruit histone deacetylase and form a complex that targets CW genes, plus ethylene biosynthetic genes (Han et al, 2016; Fu et al, 2019; Deng et al, 2022; Hu et al, 2022) (Figure 4).…”
Section: Transcriptional Regulation Of Fleshy Fruit Softeningmentioning
confidence: 99%